SEISMIC ANISOTROPY BENEATH THE NORTHERN APENNINES (ITALY): MANTLE FLOW OR LITHOSPHERE FABRIC? - Plomerová J.; Babuška V.; Vecsey L.; Margheriti L.; Pondrelli S.; Piccinini D.; Baccheschi P.; Salimbeni S.; Park J.; Levin V. (My University, 2006)
Shear-wave splitting estimates from recordings of 10 portable seismographic stations during the first year of the RETREAT seismic deployment, in combination with broadband data from the Italian national seismic network, are associated with seismic anisotropy within the upper mantle beneath the Northern Apennines. Anisotropic parameters derived from both shear-wave splitting and P travel-time residuals vary geographically and depend on event back-azimuth, reflecting complexity in the underlying mantle strain field. Variations of the splitting time delays and fast polarization seem to exclude a 2-D sublithosphere corner flow, associated with the Apennines subduction, as the main source of the inferred anisotropy. The anisotropic signal may be generated by a frozen-in fabric of the Adriatic and Tyrrhenian lithosphere domains, or by flow variations induced by episodic and fragmentary slab rollback. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTINENTAL DYNAMICS; NORTHERN APENNINES; SEISMIC ANISOTROPY; SKS BIREFRINGENCE